Ischemic stroke caused by large-artery atherosclerosis: a red flag for subclinical coronary artery disease - de Araújo, Ana Luíza Vieira; Santos, Raul D.; Bittencourt, Marcio Sommer; Dantas, Roberto Nery; Oshiro, Carlos André; Nomura, Cesar Higa; Bor-Seng-Shu, Edson; Oliveira, Marcelo de Lima; Leite, Claudia da Costa; Martin, Maria da Graça Morais; Alves, Maramelia Miranda; Silva, Gisele Sampaio; et al. (Frontiers in Neurology, 2023)
Background: The coronary calcium score (CAC) measured on chest computerized tomography is a risk marker of cardiac events and mortality. We compared CAC scores in two multiethnic groups without symptomatic coronary artery disease: subjects in the chronic phase after stroke or transient ischemic attack and at least one symptomatic stenosis ≥ 50% in the carotid or vertebrobasilar territories (Groupathero) and a control group (Groupcontrol). Methods: In this cross-sectional study, Groupathero included two subgroups: GroupExtraorIntra, with stenoses in either cervical or intracranial arteries; GroupExtra&Intra, with stenoses in at least one cervical and one intracranial artery. Groupcontrol had no history of prior stroke/transient ischemic attacks and no stenoses ≥ 50% in cervical or intracranial arteries. Age and sex were comparable in all groups. Frequencies of CAC ≥ 100 and CAC > 0 were compared between Groupathero and Groupcontrol, as well as between GroupExtraorIntr, GroupExtra&Intra and Groupcontrol, with bivariate logistic regressions. Multivariate analyses were also performed. Results: A total of 120 patients were included: 80 in Groupathero and 40 in Groupcontrol. CAC > 0 was significantly more frequent in Groupathero (85%) than Groupcontrol (OR, 4.19; 1.74-10.07; p = 0.001). Rates of CAC ≥ 100 were not significantly different between Groupathero and Groupcontrol but were significantly greater in GroupExtra&Intra (n=13) when compared to Groupcontrol (OR 4.67; 1.21-18.04; p = 0.025). In multivariate adjusted analyses, “Groupathero” and “GroupExtra&Intra” were significantly associated with CAC. Conclusions: The frequency of coronary calcification was higher in subjects with stroke caused by large artery atherosclerosis than in controls.